Reimagining a Transnational Right to the City: No Border Actions and Commoning Practices in Thessaloniki - Tsavdaroglou, Charalampos (2019)
Although there is extensive literature on State migration policies and NGO activities, there are few studies on the common struggles between refugees and local activists. This article aims to fill this research gap by focusing on the impact of the transnational No Border camp that took place in Thessaloniki in 2016. The border region of northern Greece, with its capital Thessaloniki, is at the heart of the so-called refugee crisis and it is marked by a large number of solidarity initiatives. After the sealing of the “Balkan corridor”, the Greek State relocated thousands of refugees into isolated and inappropriate camps on the outskirts of Thessaloniki. Numerous local and international initiatives, with the participation of refugees from the camps, self-organized a transnational No Border camp in the city center that challenged State policies. By claiming the right to the city, activists from all over Europe, together with refugees, built direct-democratic assemblies and organized a multitude of direct actions, demonstrations, and squats that marked the city’s social body with spatial disobedience and transnational commoning practices. Here, activism emerges as an important field of research and this article aims to contribute to activists’ literature on migration studies after 2015. The article is based on militant research and inspired by the Lefebvrian right to the city, the autonomy of migration, and common space approaches. The right to the city refers to the rights to freedom, socialization, and habitation, but also to the right to reinvent and change the city. It was recently enhanced by approaches on common spaces and the way these highlight the production of spaces based on solidarity, mutual help, common care, and direct democracy. The main findings of this study point to how the struggle of migrants when crossing physical and social borders inspires local solidarity movements for global networking and opens up new possibilities to reimagine and reinvent transnational common spaces.